Implementing open access mandates in Europe OpenAIRE study on the development of open access repository communities in Europe - Schmidt, Birgit (Universitätsverlag Göttingen, 2012)
The implementation of open access policies in Europe is a socio-technical undertaking whereby a wide range of stakeholders work together to bring out the benefits of open access for European and global research. This work provides a unique overview of national awareness of open access in 32 European countries involving all EU member states and in addition, Norway, Iceland, Croatia, Switzerland and Turkey. It describes funder and institutional open access mandates in Europe and national strategies to introduce and implement them. An overview of the current European repository infrastructures is given, including institutional and disciplinary repositories, national repository networks, information portals and support networks. This work also outlines OpenAIREplus, a continuation project which aims to widen the scope of OpenAIRE by connecting publications to contextual information, such as research data and funding information. Opportunities for collaboration in order to achieve European and global synergies are also highlighted. The OpenAIRE project, a joint collaboration among 38 partners from 27 European countries, has built up a network of open repositories providing free online access to knowledge produced by researchers receiving grants from the European Commission or the European Research Council. It provides support structures for researchers, operates an electronic infrastructure and a portal to access all user-level services and works with several subject communities. Birgit Schmidt is affi liated with Goettingen State and University Library. Iryna Kuchma is affi liated with EIFL.